2011
DOI: 10.1089/fpd.2010.0825
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase Chain Reaction Screening forSalmonellaand EnterohemorrhagicEscherichia colion Beef Products in Processing Establishments

Abstract: Pathogenic Escherichia coli strains on raw or insufficiently cooked foods are of public health concern as serious disease may result from their ingestion. Therefore, many commercial producers of beef products screen for E. coli O157:H7 before shipment. While Salmonella is not considered an adulterant on raw beef products, it is used as an indication of process control. To detect these microorganisms, rapid screening methods are often used to provide results within 8-24 hours after sampling. During 2005-2008, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 41 publications
(35 reference statements)
1
13
2
Order By: Relevance
“…There are significant differences in the percent positive rates of Salmonella in various foods of animal origin, with poultry sources consistently having the highest rates (5,11,15,29). The 2010 retail meat report from the National Antimicrobial Resistance Monitoring System (NARMS) in the United States provides the following percentages of positivity for Salmonella-.…”
mentioning
confidence: 99%
“…There are significant differences in the percent positive rates of Salmonella in various foods of animal origin, with poultry sources consistently having the highest rates (5,11,15,29). The 2010 retail meat report from the National Antimicrobial Resistance Monitoring System (NARMS) in the United States provides the following percentages of positivity for Salmonella-.…”
mentioning
confidence: 99%
“…For example, numerous studies have showed seasonal patterns in E. coli O157:H7 and Salmonella , with the peaks occurring during the summer (Hill et al . ). Spreading the sampling effort across seasons in each establishment ensures that seasonal patterns are adequately captured.…”
Section: Discussionmentioning
confidence: 97%
“…) and industry groups (Hill et al . ). In many countries, sample collection and testing is a mandatory requirement for products, such as meat and poultry, to enter commerce.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations